Excessive fatal injury among migrant children in China: inequities in safety. Issue 1 (7th January 2015) - Lin, Guozhen; Zhang, Xiao; Dong, Hong; Shen, Jichuan; Li, Ke; Zhou, Qin
Abstract : The wide variability in economic development levels among different regions in China results in the migration of millions of households to more developed areas. Death records from 2008 to 2012 of children aged 0–17 years old from the vital surveillance system of Guangzhou were used to determine if death rates were different for resident and migrant children. A total of 1358 injury-related deaths were identified with rates rising slightly from 2008 to 2012 both in resident and migrant populations. The total crude incidence rate of injury death was significantly higher among migrant households (29.50/100 000) compared with resident households (8.42/100 000). The adjusted rate in migrant households was 3.50 (95% CI 3.14 to 3.89) times higher than in resident households. Drowning and traffic crashes represented the most common causes of death and residences were the most frequent site of injury-related death for both groups of children. Migrant children were at a significantly higher risk of injury-related mortality compared with local resident children.